Performance Analysis of the Cake Ingredients Supply Chain Integration of Scor And Fuzzy AHP - Santi Nurul Azizah; Teguh Putra; Marsidah Khairani (Lembaga Penelitian dan Ilmu Pengetahuan JEPIP, 2024)
In the concept of supply chain, suppliers are one part of supply that is very important and very influential on the growth and sustainability of UMKM themselves, in the production pro- cess UMKM ABC use raw materials where UMKM must have the best suppliers in order to meet consumer satisfaction and not cause problems during the production process. The research conducted aims to determine the indicators that affect the supply chain in UMKM ABC As well as knowing how much supply chain performance value has been achieved by UMKM ABC and also providing proposals for improving performance improvement strategies for UMKM ABC. To solve these problems, supply chain performance measure- ments are carried out using the SCOR (Supply Chain Operation Refer- ence) and F-AHP (Fuzzy Analitycal Hierarcy Process) methods. This method aims to give weight to each matrix, so that performance tribute can be known that supports supply chain effectiveness. There are 12 selected performance indicators with a Supply Chain Management value of 71.20 in the good category